2013
DOI: 10.19030/ajbe.v6i3.7810
|View full text |Cite
|
Sign up to set email alerts
|

Good Bye Traditional Budgeting, Hello Rolling Forecast: Has The Time Come?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 2 publications
0
13
0
5
Order By: Relevance
“…Studies have not investigated whether differences might exist between firms adopting different forms of rolling budgets (monthly versus quarterly). Rather, the few academic articles and practitioner publications have discussed the implementation of rolling budgets in different contexts (Churchill, 1984), linked its existence to enhancing the performance of traditional budgets for operational planning and inhibiting the performance of traditional budgets for performance evaluation (Hansen and Van der Stede, 2004); noted a positive association between the usefulness of annual budgets and rolling budgets (Ekholm and Wallin, 2011;Lamoreaux, 2011), and explored the possibility of rolling budgets completely replacing annual budgets (Banham, 2011;Zeller and Metzger, 2013). Finally, Hansen (2011) conjecture that rolling budgets should raise the total volume and volatility of a firm's output, increase pay for performance sensitivity, and have an overall positive effect on performance.…”
Section: Rolling Budget -Contribution To Extant Budgeting Researchmentioning
confidence: 99%
“…Studies have not investigated whether differences might exist between firms adopting different forms of rolling budgets (monthly versus quarterly). Rather, the few academic articles and practitioner publications have discussed the implementation of rolling budgets in different contexts (Churchill, 1984), linked its existence to enhancing the performance of traditional budgets for operational planning and inhibiting the performance of traditional budgets for performance evaluation (Hansen and Van der Stede, 2004); noted a positive association between the usefulness of annual budgets and rolling budgets (Ekholm and Wallin, 2011;Lamoreaux, 2011), and explored the possibility of rolling budgets completely replacing annual budgets (Banham, 2011;Zeller and Metzger, 2013). Finally, Hansen (2011) conjecture that rolling budgets should raise the total volume and volatility of a firm's output, increase pay for performance sensitivity, and have an overall positive effect on performance.…”
Section: Rolling Budget -Contribution To Extant Budgeting Researchmentioning
confidence: 99%
“…Nors biudžetai yra finansinis įmonės planas, pagalba kontroliuoti, vertinti verslo veiklą, šiuo metu literatūroje pastebima nemažai nuomonių, kad tradiciniai biudžetai nėra palankūs ir pritaikyti dabartinei dinamiškai verslo rinkai. Tradiciniai biudžetai yra statiški, linijiniai ir metiniai (Zeller, Metzger, 2013). Todėl, pasak Z.…”
Section: Už Biudžetų Išplėstos Vadybos Sistemos Formavimosi Priežastysunclassified
“…Tiek Lietuvos, tiek užsienio autoriai yra atlikę reikšmingų tyrimų, susijusių su tradicinio biudžeto ir už biudžetų išplėstos vadybos sistemomis. Daugiausia jie analizavo tradicinių biudžetų sistemos trūkumus ir priežastis, kurios skatina šios sistemos atsisakyti (Daum, 2002;Vaznonienė, Bendaravičienė, 2012;Pietrzak, 2013;Zeller, Metzger, 2013;Klimaitienė, Jočys, 2014;Wienhold, 2015 ir kt.). Todėl imta siūlyti alternatyvą tradiciniams biudžetams -sistemą už biudžetų išplėsta vadyba.…”
unclassified
“…In these latter days, the criticism towards traditional budgeting has got larger. Neely et al (2001), Hansen et al (2003), Horvath and Sauter (2004), Pietrzak (2013), Zeller and Metzger (2013) deem that it prevents reactions to changes in the market, it cannot keep up with the changes and requirements of today's business world and it isn't useful for business management. Neely et al (2001) identified the following disadvantages of traditional budgeting: budgets are time-consuming and costly to put together; budgets are rarely strategically focused and often contradictory; they add little value, concentrate on cost reduction and not value creation; they are developed and updated infrequently, usually annually; budgets are based on unsupported assumptions and guess-work; they strengthen vertical command and control; reinforce departmental barriers rather than encourage knowledge sharing and makes people feel under-valued.…”
Section: Theoretical Framework Of Budgetingmentioning
confidence: 99%